STRATEGI KOMUNIKASI PENYIAR PROGRAMA 4 LPP RRI PADANG DALAM MEMPERTAHANKAN EKSISTENSINYA DI ERA GENERASI Z - Rahma Sari Rahayu; Fajri Ahmad (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This study aims to find out the communication strategy and constraints of RRI Padang program 4 broadcasters in the era of generation z. This research is a qualitative research with a descriptive approach, with data collection techniques in the form of observation, interviews and documentation. The results of this study provide findings covering four programs in program 4, as for the Communication Strategy of Broadcasters Program 4 LPP RRI Padang in Maintaining Its Existence in the Generation Z Era, namely: communication strategy of the broadcaster in the "Dendang Dangdut" program in this program, listeners are free to request songs and send greetings with other listeners. Second, the communication strategy of the broadcaster program 4 in the "Salam Bajawek" program in this program listeners are free to request minang songs of choice. Third, the communication strategy of the broadcaster in the program "kato bajawek in pantun" in this program is free for listeners to exchange rhymes with the host or resource persons presented in the studio, and the strategy of broadcaster communication in the program "Minangkabau local wisdom" in this program is an interactive dialogue by presenting intellectual speakers, and through this program can revive the wisdom of Minangkabau culture, And the obstacles faced are in the form of external obstacles in the form of resource persons not being able to attend the studio, making the program unable to be run or the program broadcast online, and the internal obstacles are in the form of emotional and mental disturbances from a broadcaster or it can be from the tool. Keywords : Communication Strategy, Radio Announcer, Generation Z